IMPLEMENTATION OF ARTICLE 2 PARAGRAPH (3) LETTER D OF MINISTER OF TRADE REGULATION NUMBER 18 OF 2021 ON THE PROHIBITION OF USED CLOTHING IMPORTS: A FIQH SIYASAH PERSPECTIVE - Kalya Bassya Irana; Iwan Iwan (Program Pascasarjana UIN Sumatera Utara, 2026)
The trade in imported used clothing continues to occur in various regions of Indonesia despite being prohibited under the Regulation of the Minister of Trade of the Republic of Indonesia Number 18 of 2021 concerning Prohibited Export and Import Goods. Tanjung Balai City, a coastal area located along the international shipping route of the Malacca Strait, is particularly vulnerable to the illegal entry of imported used clothing through unofficial routes. This study aims to analyze the implementation of Article 2 paragraph (3) letter (d) of the Minister of Trade Regulation Number 18 of 2021 regarding the trade of imported used clothing in Tanjung Balai City, identify the factors contributing to the persistence of this practice, and examine it from the perspective of Fiqh Siyasah. This research employs an empirical legal method with a qualitative approach. Primary data were collected through observation and semi-structured interviews with officials of the Teluk Nibung Customs Office, used clothing traders, and consumers, while secondary data were obtained from legislation, books, scholarly journals, and supporting documents. Data were analyzed using the Miles, Huberman, and Saldaña interactive model and interpreted through the theories of policy implementation, Lawrence M. Friedman's legal system theory, and the concept of Siyāsah Tanfīdziyyah. The findings indicate that the implementation of the prohibition policy has not been fully effective due to limited policy dissemination, inadequate supervision, high consumer demand, and traders' economic dependence on the business. From the perspective of Fiqh Siyasah, the policy is consistent with the principles of Siyāsah Tanfīdziyyah and maslahah; however, its implementation requires stronger supervision, economic empowerment, and greater public legal awareness to achieve the intended public welfare.